Grain size effect on the structural, electrical, magnetic and magneto-transport properties of Pr-A-Mn-O (A = Sr, Ba, Na, K) nanomanganite - Ng, Siau Wei (2017)
Colossal magnetoresistance (CMR) effect in the manganese oxide compounds are nowadays a very potential technological applications in the information storage, sensors, magnetic sensing devices and magnetic refrigeration. These CMR effects can be tuned up as the grains size is reduced to nanometers. However, the physics phenomenons of nano-sized manganites were still not yet fully understood. Although a number of works had been carried out on the effect of grain size (in nanometric regime) towards its physical properties, but less research work had been put attention in praseodymium based nano-manganese so far. Therefore, in this work, Pr0.67(Sr, Ba)0.33MnO3 and Pr0.85(Na, K)0.15MnO3 had been synthesized by sol-gel technique and sintered from 600oC to 1000oC to investigate the influence of grain size reduction from micro to nano-size. XRD results showed that all samples are polycrystalline with orthorhombic structure and no significant lattice distortion was observed as the sintering temperature increased. As the grain size increase from nano to micron-size, the resistivity of Pr0.67Sr0.33MnO3 (PSMO) and Pr0.67Ba0.33MnO3 (PBMO) decreased and Tp shifted to higher value while Pr0.85Na0.15MnO3 (PNMO) showed semiconductor behavior where Tp were estimated to be lower than 80 K. However, for Pr0.85K0.15MnO3 (PKMO), the Tp and resistivity shifted to lower value with increasing grain size. This variation was due to the different of grain shape and grain distribution. Besides, the Tc was shifted to higher value for PSMO (278 K to 295 K), PBMO (140 K to 188 K) and PKMO (124 K to 140 K) systems as grain size increase. Substitute A-site with divalent or monovalent produce a Jahn Teller distortion of MnO6 octahedron. By changing the ionic radius of A-site, the Mn-O-Mn angles and Mn-O lengths can be modified and hence affect the physical properties in the manganites system. From this work, we found that as the manganites system replace with monovalent, the Tc and Tp shifted to lower temperature (< 200 K) and the magnitude of MR around room temperature was relatively smaller compare with divalent system. Besides, higher value of resistivity is observed for monovalent system as compare with divalent system. In general, every manganites system there exist an optimum grain size distribution at which the MR or LFMR reaches a maximum. This optimal grain size may vary for different system and may also depend on the synthesis technique. Out of all the four series samples under investigation, Pr0.85K0.15MnO3 (PKS6) with average grain size of 51 nm was found to exhibit highest %MR of – 53.3% (at 80 K with magnetic field of 1 Tesla). However, the highest %MR value at room temperature (300 K) was – 2.39% for sample Pr0.67Sr0.33MnO3 (PSS7 with average grain size of 37 nm). From a practical view-point, the high %MR values are beneficial in magnetoelectronic sensing devices.